GABA, but Not Bestrophin-1, Is Localized in Astroglial Processes in the Mouse Hippocampus and the Cerebellum - Ormel, Lasse; Lauritzen, Knut H.; Schreiber, Rainer; Kunzelmann, Karl; Gundersen, Vidar (Frontiers in Molecular Neuroscience, 2020)
GABA is proposed to act as a gliotransmitter in the brain. Differences in GABA release from astroglia are thought to underlie differences in tonic inhibition between the cerebellum and the CA1 hippocampus. Here we used quantitative immunogold cytochemistry to localise and compare the levels of GABA in astroglia in these brain regions. We found that the density of GABA immunogold particles was similar in delicate processes of Bergman glia in the cerebellum and astrocytes in the CA1 hippocampus. The astrocytic GABA release is proposed to be mediated by, among others, the Ca2+ activated Cl- channel bestrophin-1. The bestrophin-1 antibodies did not show any significant bestrophin-1 signal in the brain of wt mice, nor in bestrophin-1 knockout mice. The bestrophin-1 signal was low both on Western blots and immunofluorescence laser scanning microscopic images. These results suggest that GABA is localised in astroglia, but in similar concentrations in the cerebellum and CA1 hippocampus, and thus cannot account for differences in tonic inhibition between these brain regions. Furthermore, our data seem to suggest that the GABA release from astroglia previously observed in the hippocampus and cerebellum occurs via mechanisms other than bestrophin-1.